Simeprevir with peginterferon/ribavirin for treatment of chronic hepatitis C virus genotype 1 infection: pooled safety analysis from Phase IIb and III studies. Issue 4 (3rd November 2014) - Manns, M. P.; Fried, M. W.; Zeuzem, S.; Jacobson, I. M.; Forns, X.; Poordad, F.; Peeters, M.; Fu, M.; Lenz, O.; Ouwerkerk‐Mahadevan, S.; Jessner, W.; Scott, J. A.; et al.
Summary This pooled analysis of five Phase IIb and III studies evaluated the safety and tolerability of simeprevir, a once daily, oral hepatitis C virus (HCV) NS3/4A protease inhibitor. Data were summarised for patients who received simeprevir 150 mg once daily (n = 924) or placebo (n = 540) plus pegylated interferon‐α/ribavirin for 12 weeks. During the first 12 weeks of treatment, few patients discontinued simeprevir or placebo due to adverse events (AEs) (both 2.2%). Pruritus (23.8% vs 17.4%), rash (any; 22.9% vs 16.7%) and photosensitivity (3.2% vs 0.6%) [Correction added on 16 January 2015, after first online publication: In the above sentence, the values in 'Photosensitivity' were previously incorrect and have now been changed to 3.2% vs 0.6%.] were more prevalent in the simeprevir vs the placebo groups. Most AEs were grade 1/2 (72.4% for simeprevir vs 71.3% for placebo). All grade 3/4 AEs occurred in <5.0% of patients, except neutropenia (9.8% vs 7.6%). Overall incidence of neutropenia was similar (17.3% vs 15.7%). Incidence of anaemia was 13.2% for simeprevir vs 10.9% for placebo, and incidence of increased bilirubin was 8.4% vs 2.8%. Bilirubin increases were mild‐to‐moderate and transient without concurrent transaminase increases or association with hepatic injury. Safety and tolerability did not vary with METAVIR score, although increased bilirubin and anaemia were more frequent in simeprevir‐treated patients with METAVIR F4 (increased bilirubin, 13.0% vs 3.3%; anaemia, 19.0% vs 14.8%). Serious AEs were infrequent (2.1% for simeprevir vs 3.0% for placebo). No deaths were reported during the first 12 weeks of treatment. Patient‐reported fatigue and other outcomes were comparable for both groups, but were of shorter duration for simeprevir due to the use of response‐guided therapy. Simeprevir is well tolerated in HCV genotype 1‐infected patients.